2015
DOI: 10.1080/01694243.2015.1087254
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mechanical and air-particle cleansing protocols of provisional cement on immediate dentin sealing layer and subsequent adhesion of resin composite cement

Abstract: Originally published at: Özcan, Mutlu; Lamperti, Sofia (2015). Effect of mechanical and air-particle cleansing protocols of provisional cement on immediate dentin sealing layer and subsequent adhesion of resin composite cement. Journal of Adhesion Science and Technology, 29(24) Zürich, 2 Abstract: Immediate dentin sealing (IDS) could avoid contamination of dentin from impression material and provisional cement but prior to final cementation of indirect restorations, removal of the provisional cement may dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 24 publications
(28 reference statements)
0
21
0
Order By: Relevance
“…Within CL Group, however, µSBS values were generally lower, probably highlighting a more difficult removal of particles of the resin-based, light-cured luting agent. values was found between the removal of temporary cements with a prophylaxis paste or with two different sandblasting regimens (2 or 3.5 bar pressure) [19]. Abo-Hamar et al also identified a comparable efficacy between cleanings with sandblasting and curettes [25].…”
Section: Several Authors Have Supported the Ids Technique For Cementamentioning
confidence: 98%
See 4 more Smart Citations
“…Within CL Group, however, µSBS values were generally lower, probably highlighting a more difficult removal of particles of the resin-based, light-cured luting agent. values was found between the removal of temporary cements with a prophylaxis paste or with two different sandblasting regimens (2 or 3.5 bar pressure) [19]. Abo-Hamar et al also identified a comparable efficacy between cleanings with sandblasting and curettes [25].…”
Section: Several Authors Have Supported the Ids Technique For Cementamentioning
confidence: 98%
“…On the other hand, it should be emphasized that a prolonged, overextended action of some surface treatments might also produce obscuration of dentinal tubule openings due to formation of additional smear layers, finally providing less reliable adhesion results [26]. That problem is also observed with other more aggressive mechanical methods involving finishing or tungsten carbide burs, that might impair precise fitting of indirect restorations [19]; for this reason, they are not suggested for surface cleanings, and where not included in the present study. One previous research have investigated the effect of mechanical treatments (i.e: polishing and air abrasion) on IDS layers [27]: as revealed by SEM analysis, the amount of hybridized layer that was removed with that cleaning methods was not uniform (11.94 +/-16.46 µm), and a great range of values was recorded (0 to 145 µm); however, in the majority of cases, a minimum thickness of adhesive layer was preserved.…”
Section: Several Authors Have Supported the Ids Technique For Cementamentioning
confidence: 99%
See 3 more Smart Citations